Terapeutická komunita ako model práce na víkendových pobytoch pre deti s poruchami správania a ich rodičov - Škoviera, Albín (Univerzita Pardubice, 2012)
This contribution stems out of three basic theses. The first thesis asserts that reeducation of children is not well manageable without involving parents or family into it as they are inseparable elements of the problem. The second thesis affirms that efficient therapeutic and educational work is a combination of parallel work with family and children and cooperative work with family and children. That is precisely how integrating and synthetising therapeutic approaches can be used effectively. The concept of the third thesis is that an optimum model for this kind of work is a well-set therapeutic community. Not only the level of a whole community system is concerned - also the level of actual community meetings. The purpose of this contribution is to inform about the setting and functionality of this kind of system.
Therapeutic community as a model of work during weekend camps for children with behaviour disorders and their parents
Keywords: therapeutic community; socio-therapeutic community club; parental group; childrens group; team